Attosecond Resolved Interferometric Electric-field Sampling (ARIES) - Wyatt, A; Schiavi, A; Walmsley, I; Witting, T; Fabris, D; Matia-Hernando, P; Marangos, J; Tisch, J (University of Oxford, 2016)
This data set contains raw and processed data for the first proof-of-principle measurements of the ARIES technique. The method and results are fully described in the paper "Attosecond sampling of arbitrary optical waveforms", which has been accepted for publication in Optica (Feb 2016).